A catalytic cracking catalyst for woody oil and non-metal modified molecular sieve and its preparation method and application
By controlling the loading morphology of non-metallic elements on a substrate molecular sieve, a modified molecular sieve catalyst with a pore structure and acid-base properties was constructed. This solved the problems of pore matching degree and complex reaction pathways in the catalytic cracking of woody oils and achieved the effect of efficient preparation of hydrocarbon-rich biofuels.
Patent Information
- Application Number
- CN202410469790.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-18
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-04-18
AI Technical Summary
Existing catalysts for the catalytic cracking of woody oils suffer from problems such as poor matching between pore structure and reactant molecular size, unreasonable acidic site properties, and a wide variety of potential active sites leading to low catalytic selectivity, unsatisfactory catalyst lifetime, and complex reaction pathways.
By strictly controlling the alkaline etching-impregnation-calcination process, the loading morphology of non-metallic elements on the substrate molecular sieve is regulated, and modified molecular sieve catalysts with pore structure and acid-base properties are constructed to reduce the types of potential active sites. Phosphorus or boron is used as non-metallic elements to synergize with substrate molecular sieves such as ZSM-5, HZSM-5, SAPO-11 or SAPO-34.
A modified molecular sieve catalyst with high activity, high stability and good anti-carbon deposition ability was developed. The overall yield of hydrocarbon-rich biofuels produced by catalyzing the production of sclerotium truncatum oil reached 70 wt%, and the yield of C10-C18 hydrocarbon-rich biofuels per unit catalyst per unit time reached 35 wt%/(g·h).
Smart Images

Figure CN118341479B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a non-metallic modified molecular sieve catalyst, specifically to a non-metallic modified molecular sieve catalyst for the catalytic cracking of woody oils and their preparation method and application, belonging to the field of chemical synthesis. Background Technology
[0002] The global energy crisis and climate change have spurred unprecedented growth in renewable energy. According to the International Energy Agency, global renewable energy production capacity is projected to equal the total production of the past 20 years over the next five years, and global demand for biofuels may exceed 10 exojoules by 2050. As the only renewable carbon source, the large-scale development and application of biomass energy is a crucial pathway to accelerating the green and low-carbon energy transition and achieving a net-zero economy. Against this backdrop, developing biofuel technologies using woody oilseeds such as *Gnaphalium affine* oil as feedstock is of great significance for optimizing my country's energy structure and achieving its dual-carbon goals.
[0003] Currently, the main method for producing biodiesel from *Pterocarya stenoptera* oil is transesterification. However, this method results in products with drawbacks such as poor low-temperature fluidity, low energy density, high acid value, and susceptibility to oxidation and deterioration. In contrast, leveraging the advantages of thermochemical conversion and refining *Pterocarya stenoptera* oil through catalytic cracking can yield products with higher compatibility with petroleum-based diesel, while also significantly reducing production costs and environmental impact.
[0004] However, given the significant differences in some physicochemical properties (such as oxygen content, water content, acid value, and molecular size) between woody oils like *Pterocarya stenoptera* oil and petroleum fractions, their catalytic cracking process involves not only cracking and polymerization but also more complex chemical reactions such as decarbonylation, decarboxylation, and dehydration. Therefore, the catalytic cracking process of woody oils places higher demands on the structural design of the corresponding catalysts, primarily through the synergistic regulation of pore structure and acidic sites. This means not only ensuring the smooth mass transfer of large molecules such as triglycerides within the pores but also matching acidic active sites of appropriate strength and density to promote the efficient execution of decarbonylation, decarboxylation, and dehydration processes.
[0005] Currently, researchers primarily use traditional catalytic cracking catalysts such as ZSM-5 molecular sieves as a base, conducting extensive research on pore structure and acidic site regulation, and gradually forming a catalyst preparation strategy of "alkali etching desilication and pore expansion - metal loading modification". While this catalyst system has effectively improved the yield and quality of the product oil, there are still two issues that urgently need improvement for its subsequent widespread application:
[0006] 1) The problem of poor matching between the molecular sieve pore structure and the reactant molecule size. Studies have found that the alkaline etching desilication method is difficult to achieve the control and selective construction of pore structures of specific sizes. The resulting pore size is usually above 10 nm, which is not well matched with the reactant molecule size (about 4 nm). In addition, the desilication process essentially destroys the structural stability of the molecular sieve and sacrifices some acidic sites, which ultimately leads to problems such as low selectivity of the target product and unsatisfactory catalyst lifetime.
[0007] 2) The difficulty in identifying reaction pathways and analyzing catalytic mechanisms. As mentioned earlier, the reaction network of woody oil catalytic cracking is relatively complex. At the same time, the metal-supported modified molecular sieve catalyst has a variety of potential active sites (lattice oxygen, crystal surface defects, etc.) in addition to acidic sites, which leads to complex reaction pathways in the catalytic cracking process, thereby increasing the difficulty in analyzing the catalytic mechanism.
[0008] Therefore, constructing modified molecular sieve catalysts with high pore size matching with reactant molecules, reasonable acidic site properties, and few types of potential active sites is an important way to deepen the understanding of the catalytic cracking process of woody oils and promote the development of related industries. Summary of the Invention
[0009] To address the problems existing in the prior art, the first objective of this invention is to provide a non-metallic modified molecular sieve catalyst for the catalytic cracking of woody oils. This catalyst is based on the synergistic effect between the base molecular sieve and the non-metallic elements. Without affecting the molecular sieve structure, the pore structure and acid-base properties are controlled to reduce the types of potential active sites, thereby constructing a modified molecular sieve catalyst with high activity, high stability and good anti-carbon deposition ability.
[0010] The second objective of this invention is to provide a method for preparing a non-metallic modified molecular sieve catalyst for the catalytic cracking of woody oils. This method, by strictly controlling the alkaline etching-impregnation-calcination process conditions, regulates the loading morphology of non-metallic elements on the substrate molecular sieve, effectively solving the problems of poor matching degree between the pores and reactant molecules, weak controllability of product component categories and corresponding carbon chain lengths, and difficulty in elucidating the mechanism of action in the prior art.
[0011] The third objective of this invention is to provide an application of a non-metallic modified molecular sieve catalyst for the catalytic cracking of woody oils, specifically for the production of hydrocarbon-rich biofuels from *Scleroderma purpurea* oil. Based on the molecular sieve catalyst provided by this invention, satisfactory catalytic activity, selectivity, and stability are observed in the catalytic cracking reaction of *Scleroderma purpurea* oil. Testing shows that this catalyst can achieve a comprehensive yield of 70 wt% of C10–C18 hydrocarbon fuels from the catalytic cracking of *Scleroderma purpurea* oil to hydrocarbon-rich biofuels, with a yield of 35 wt% / (g·h) of C10–C18 hydrocarbon-rich biofuels achieved per unit catalyst per unit time.
[0012] To achieve the above-mentioned technical objectives, the present invention provides a non-metallic modified molecular sieve catalyst for the catalytic cracking of woody oils, comprising a substrate molecular sieve and non-metallic elements supported on its surface; the non-metallic elements are phosphorus or boron, and their mass percentage content is 0.5% to 8.0% of the total mass of the catalyst.
[0013] As a preferred embodiment, the non-metallic element content is 3.0% to 5.0% of the total mass of the catalyst.
[0014] As a preferred embodiment, the substrate molecular sieve is one of ZSM-5, HZSM-5, SAPO-11, and SAPO-34. More preferably, the substrate molecular sieve is one of ZSM-5, HZSM-5, SAPO-11, or SAPO-34 modified with BO-Al / B-OH or P=O / P-OH / PO-Al.
[0015] The primary innovation of this invention lies in utilizing the modified BO / B-OH or P=O / P-OH molecular sieve three-dimensional materials as a catalyst for the catalytic cracking of woody oilseeds. This modified molecular catalyst exhibits high catalytic activity in the catalytic cracking reaction of *Pterocarya stenoptera*, effectively improving not only the yield of C10–C18 hydrocarbon-rich biofuels but also the catalyst's stability.
[0016] As a preferred embodiment, the phosphorus source of the non-metallic element phosphorus is one of hydroxyethylidene diphosphate monohydrate, hexachlorotriphosphazene, and ammonium dihydrogen phosphate.
[0017] As a preferred embodiment, the boron source for the non-metallic element boron is boric acid or boron oxide.
[0018] As a preferred embodiment, the catalyst has an internal pore size larger than the substrate molecular sieve size, ranging from 3 to 10 nm, and a specific surface area of 6 to 100 m². 2 / g.
[0019] This invention also provides a method for preparing a non-metallic modified molecular sieve catalyst for the catalytic cracking of woody oils, wherein the substrate molecular sieve is alkali-etched, then fully impregnated in a non-metallic element solution, and then calcined under a protective atmosphere to obtain the catalyst.
[0020] As a preferred embodiment, the alkaline etching treatment is carried out at room temperature, and the alkaline etchant is a strongly alkaline solution with a concentration of 0.2–0.5 mol / L.
[0021] As a preferred embodiment, the conditions for thorough impregnation are: a temperature of 20–80°C, a non-metallic element solution concentration of 0.5–5.0 wt%, and a time of 0.5–2 h. More preferably, the conditions for thorough impregnation are: a temperature of 50–70°C, a non-metallic element solution concentration of 1.0–3.0 wt%, and a time of 1 h.
[0022] As a preferred embodiment, the protective atmosphere is nitrogen and / or argon. More preferably, the protective atmosphere is nitrogen.
[0023] As a preferred embodiment, the calcination conditions are: a temperature of 400–600°C and a time of 2–4 hours. More preferably, the calcination conditions are: a temperature of 450–500°C and a time of 3 hours.
[0024] This invention also provides an application of a non-metallic modified molecular sieve catalyst for the catalytic cracking of woody oils, used for the catalytic cracking of *Pterocarya stenoptera* oil to produce hydrocarbon-rich biofuels. The process is as follows: under an oxygen-free atmosphere, *Pterocarya stenoptera* oil is pumped into a catalytic bed containing the above-mentioned molecular sieve catalyst for heated catalytic cracking.
[0025] As a preferred embodiment, the liquid hourly space velocity (LHSV) of the prickly ash oil pumped in is 0.10–10.00 h⁻¹. -1 .
[0026] As a preferred embodiment, the catalyst bed comprises the aforementioned molecular sieve catalyst and inert quartz sand.
[0027] In this invention, the inert silica sand used to fill the catalyst bed only serves to dilute the catalyst and reduce the pressure drop in the bed; it does not possess catalytic activity. Therefore, silica sand can be replaced by other inert bed filler materials well-known in the industry, such as silicon carbide. Furthermore, there are no special requirements for the amount of non-metallic modified molecular sieve catalyst and silica sand; they can be flexibly adjusted as needed.
[0028] As a preferred embodiment, the temperature of the heated catalytic cracking is 350–500°C.
[0029] The catalyst provided by this invention differs from traditional metal-modified catalysts. Non-metallic modification can effectively modulate the acid-base properties of molecular sieve materials without introducing new crystal structures, thereby enhancing their performance in the catalytic cracking of heavy hydrocarbons such as n-dodecane. Furthermore, non-metallic modification offers advantages such as low cost, good stability, and low pollution. The catalyst provided by this invention, starting from pore structure adjustment and acidic site property control, employs a non-metallic modification strategy to prepare non-metallic modified molecular sieve catalysts with clearly defined active site types, and adjustable and controllable strength and quantity, while ensuring that the material's crystal structure remains unchanged and the pore structure is reasonable. This endows the catalyst with superior catalytic activity, stability, and resistance to carbon deposition.
[0030] Compared with the prior art, the beneficial technical effects of the technical solution of the present invention are as follows:
[0031] 1) The modified molecular sieve catalyst provided by this invention is based on the synergistic effect between the base molecular sieve and non-metallic elements. Without affecting the molecular sieve structure, the pore structure and acid-base properties are controlled to reduce the types of potential active sites, thereby constructing a modified molecular sieve catalyst with high activity, high stability and good anti-carbon deposition ability.
[0032] 2) The preparation method provided by the present invention effectively solves the problems of poor matching degree between the pores of the modified molecular sieve catalyst and the reactant molecules, weak controllability of product component categories and corresponding carbon chain lengths, and difficulty in elucidating the mechanism of action in the prior art by strictly controlling the alkaline etching-impregnation-calcination process conditions.
[0033] 3) The molecular sieve catalyst provided by this invention exhibits satisfactory catalytic activity, catalytic selectivity and stability for the catalytic cracking reaction of *Scleroderma purpurea* oil. According to the test, the catalyst can achieve a comprehensive yield of C10-C18 hydrocarbon fuels of up to 70 wt% for the catalytic cracking of *Scleroderma purpurea* oil to produce hydrocarbon-rich biofuels, and the yield of C10-C18 hydrocarbon-rich biofuels per unit catalyst per unit time can reach 35 wt% / (g·h). Attached Figure Description
[0034] Figure 1 The BET diagrams are for the phosphorus-modified molecular sieve catalysts provided in Examples 1, 5, 6 and Comparative Example 1 of this invention.
[0035] Figure 2 The XRD patterns are of the phosphorus-modified molecular sieve catalysts provided in Examples 1, 7 and Comparative Example 1 of this invention.
[0036] Figure 3 The above are FT-IR images of the phosphorus-modified molecular sieve catalysts provided in Example 1 and Comparative Example 1 of this invention.
[0037] Figure 4 The above are NH3-TPD diagrams of the phosphorus-modified molecular sieve catalysts provided in Example 1 and Comparative Example 1 of this invention.
[0038] Figure 5 The XPS total spectrum and P2p spectrum of the phosphorus-modified molecular sieve catalyst provided in Example 1 of this invention are shown below; wherein, Figure 5 (a) is the overall spectrum of the phosphorus-modified molecular sieve catalysts provided in Example 1 and Comparative Example 1 of the present invention. Figure 5 (b) is the P 2p spectrum of the phosphorus-modified molecular sieve catalyst provided in Example 1 of the present invention. Detailed Implementation
[0039] The technical solution of the present invention will be further described below with reference to specific embodiments. It is worth noting that the following examples are only used to explain the present invention and do not constitute a limitation of the present invention.
[0040] Example 1
[0041] The catalytic cracking reaction of *Gnaphalium affine* oil was carried out in an atmospheric pressure fixed-bed reactor. The specific operating steps are as follows:
[0042] (1) Alkali etching: Weigh 2.0 g NaOH and dissolve it in 100 mL of deionized water. Then add 5.0 g of 20-40 mesh ZSM-5 (silicon-to-aluminum ratio = 50) particles, set the stirring speed to 300 rpm, and immerse the sample at room temperature for 1 h. Subsequently, use dilute acid and deionized water alternately for filtration to remove aluminum material and silicate deposits on the skeleton caused during the alkali treatment, so as to avoid clogging the pores. Finally, place the filtered sample in an oven at 110 ℃ and dry for 6 h.
[0043] (2) Impregnation: Prepare 50 mL of 0.25 mol / L hydroxyethylidene diphosphonic acid monohydrate solution, add 3.0 g of ZSM-5 molecular sieve with a silicon-to-aluminum ratio of 50 under the conditions of 65℃ oil bath and 300 rpm stirring, and impregnate for 2 h. Then, cool the sample in an ice bath and wash it with deionized water until the filtrate is neutral. Dry it at 110℃ for 6 h.
[0044] (3) Calcination: The obtained sample was placed in a tube furnace and heated to 500℃ at a heating rate of 5℃ / min under N2 atmosphere protection. The sample was calcined for 2h to obtain the non-metallic phosphorus modified ZSM-5 molecular sieve catalyst, named: 0.25HEDP@ZSM-5(50), where 0.25 represents the concentration of phosphorus source solution, HEDP represents the type of phosphorus source, and 50 represents the silicon-aluminum ratio of ZSM-5 molecular sieve.
[0045] First, 1.0 g of catalyst was weighed and placed into a stainless steel high-pressure reaction tube, and the airtightness of the equipment was checked. Then, under a N2 atmosphere at a rate of 5 °C / min, the temperature was increased from room temperature to the reaction temperature and stabilized for 30 min to eliminate temperature differences in the reaction system. The reactant, *Gnaphalium affine* oil, was pumped into the reaction tube using a syringe pump at a flow rate of 0.125 mL / min, and the product was cooled in a condenser. After 2 h of reaction, the valve was opened to collect the product, and the components and relative contents of the product oil were analyzed by gas chromatography-mass spectrometry (GC-MS). The chromatographic column was an HP-5MS (30 m × 0.25 mm × 0.25 μm), with an injection volume of 0.5 μL, a column flow rate of 1 mL / min, a split ratio of 50:1, and a temperature program of: initial temperature 40 °C, increased to 80 °C at a rate of 3 °C / min, and then increased to 260 °C at a rate of 5 °C / min. The mass spectrometry conditions were as follows: ionization mode EI, electron energy 70 eV, transfer line temperature 250℃, ion source temperature 230℃, quadrupole temperature 250℃, mass range 35–550 m / z, and comparative analysis was performed using the Nist08.1 standard spectral library. In addition, changes in the mass and functional groups of different types of fatty acids were detected and verified using a thermogravimetric-Fourier transform infrared (TG-FTIR) system.
[0046] Using the catalyst performance testing method described in Example 1, the catalyst performance was measured as follows: the overall yield of C10-C18 hydrocarbon fuels was 70.36 wt%, and the yield of C10-C18 hydrocarbon-rich biofuels achieved per unit catalyst per unit time was 35.18 wt% / (g·h). After three cycles, the yield of C10-C18 hydrocarbon-rich biofuels achieved per unit catalyst per unit time was 34.98 wt% / (g·h).
[0047] Example 2
[0048] (1) Alkali etching: Weigh 2.0 g NaOH and dissolve it in 100 mL of deionized water. Then add 5.0 g of 20-40 mesh ZSM-5 (silicon-to-aluminum ratio = 100) particles. Set the stirring speed to 300 rpm and immerse the sample at room temperature for 1 h. Subsequently, use dilute acid and deionized water alternately for filtration to remove aluminum material and silicate deposits on the skeleton caused during the alkali treatment, so as to avoid clogging the pores. Finally, place the filtered sample in an oven at 110 ℃ and dry for 6 h.
[0049] (2) Impregnation: Prepare 50 mL of 0.25 mol / L hydroxyethylidene diphosphonic acid monohydrate solution, add 3.0 g of ZSM-5 molecular sieve with a silicon-to-aluminum ratio of 50 under the conditions of 65℃ oil bath and 300 rpm stirring, and impregnate for 2 h. Then, cool the sample in an ice bath and wash it with deionized water until the filtrate is neutral. Dry it at 110℃ for 6 h.
[0050] (3) Calcination: The obtained sample was placed in a tube furnace and heated to 500℃ at a heating rate of 5℃ / min under N2 atmosphere protection. The sample was calcined for 2h to obtain the non-metallic phosphorus modified ZSM-5 molecular sieve catalyst, named: 0.25HEDP@ZSM-5(100), where 0.25 represents the concentration of phosphorus source solution, HEDP represents the type of phosphorus source, and 100 represents the silicon-aluminum ratio of ZSM-5 molecular sieve.
[0051] Using the catalyst performance testing method in Example 1, the catalyst performance was measured as follows: the overall yield of C10-C18 hydrocarbon fuels was 66.29 wt%, and the yield of C10-C18 hydrocarbon-rich biofuels per unit catalyst per unit time was 33.15 wt% / (g·h).
[0052] Example 3
[0053] (1) Alkali etching: Weigh 2.0 g NaOH and dissolve it in 100 mL of deionized water. Then add 5.0 g of 20-40 mesh ZSM-5 (silicon-to-aluminum ratio = 50) particles, set the stirring speed to 300 rpm, and immerse the sample at room temperature for 1 h. Subsequently, use dilute acid and deionized water alternately for filtration to remove aluminum material and silicate deposits on the skeleton caused during the alkali treatment, so as to avoid clogging the pores. Finally, place the filtered sample in an oven at 110 ℃ and dry for 6 h.
[0054] (2) Impregnation: Prepare 50 mL of 0.25 mol / L hexachlorotriphosphazene solution, add 3.0 g of ZSM-5 molecular sieve with a silicon-to-aluminum ratio of 50 under the conditions of 65℃ oil bath and 300 rpm stirring, and impregnate for 2 h. Then, cool the sample in an ice bath and wash it with deionized water until the filtrate is neutral. Dry it at 110℃ for 6 h.
[0055] (3) Calcination: The obtained sample was placed in a tube furnace and heated to 500℃ at a heating rate of 5℃ / min under N2 atmosphere protection. The sample was calcined for 2h to obtain the non-metallic phosphorus modified ZSM-5 molecular sieve catalyst, named: 0.25HCCP@ZSM-5(50), where 0.25 represents the concentration of phosphorus source solution, HCCP represents the type of phosphorus source, and 50 represents the silicon-aluminum ratio of ZSM-5 molecular sieve.
[0056] Using the catalyst performance testing method in Example 1, the catalyst performance was measured as follows: the overall yield of C10-C18 hydrocarbon fuels was 69.05 wt%, and the yield of C10-C18 hydrocarbon-rich biofuels per unit catalyst per unit time was 34.53 wt% / (g·h).
[0057] Example 4
[0058] (1) Alkali etching: Weigh 2.0 g NaOH and dissolve it in 100 mL of deionized water. Then add 5.0 g of 20-40 mesh ZSM-5 (silicon-to-aluminum ratio = 50) particles, set the stirring speed to 300 rpm, and immerse the sample at room temperature for 1 h. Subsequently, use dilute acid and deionized water alternately for filtration to remove aluminum material and silicate deposits on the skeleton caused during the alkali treatment, so as to avoid clogging the pores. Finally, place the filtered sample in an oven at 110 ℃ and dry for 6 h.
[0059] (2) Impregnation: Prepare 50 mL of 0.25 mol / L ammonium dihydrogen phosphate solution, add 3.0 g of ZSM-5 molecular sieve with a silicon-to-aluminum ratio of 50 under the conditions of 65℃ oil bath and 300 rpm stirring, and impregnate for 2 h. Then, cool the sample in an ice bath and wash it with deionized water until the filtrate is neutral. Dry it at 110℃ for 6 h.
[0060] (3) Calcination: The obtained sample was placed in a tube furnace and heated to 500℃ at a heating rate of 5℃ / min under N2 atmosphere protection. The sample was calcined for 2h to obtain the non-metallic phosphorus modified ZSM-5 molecular sieve catalyst, named: 0.25MAP@ZSM-5(50), where 0.25 represents the concentration of phosphorus source solution, MAP represents the type of phosphorus source, and 50 represents the silicon-aluminum ratio of ZSM-5 molecular sieve.
[0061] Using the catalyst performance testing method in Example 1, the catalyst performance was measured as follows: the overall yield of C10-C18 hydrocarbon fuels was 58.78 wt%, and the yield of C10-C18 hydrocarbon-rich biofuels per unit time on the catalyst was 29.39 wt% / (g·h).
[0062] Example 5
[0063] (1) Alkali etching: Weigh 2.0 g NaOH and dissolve it in 100 mL of deionized water. Then add 5.0 g of 20-40 mesh ZSM-5 (silicon-to-aluminum ratio = 50) particles, set the stirring speed to 300 rpm, and immerse the sample at room temperature for 1 h. Subsequently, use dilute acid and deionized water alternately for filtration to remove aluminum material and silicate deposits on the skeleton caused during the alkali treatment, so as to avoid clogging the pores. Finally, place the filtered sample in an oven at 110 ℃ and dry for 6 h.
[0064] (2) Impregnation: Prepare 50 mL of 0.12 mol / L hydroxyethylidene diphosphonic acid monohydrate solution, add 3.0 g of ZSM-5 molecular sieve with a silicon-to-aluminum ratio of 50 under the conditions of 65℃ oil bath and 300 rpm stirring, and impregnate for 2 h. Then, cool the sample in an ice bath and wash it with deionized water until the filtrate is neutral. Dry it at 110℃ for 6 h.
[0065] (3) Calcination: The obtained sample was placed in a tube furnace and heated to 500℃ at a heating rate of 5℃ / min under N2 atmosphere protection. The sample was calcined for 2h to obtain the non-metallic phosphorus modified ZSM-5 molecular sieve catalyst, named: 0.12HEDP@ZSM-5(50), where 0.12 represents the concentration of phosphorus source solution, HEDP represents the type of phosphorus source, and 50 represents the silicon-aluminum ratio of ZSM-5 molecular sieve.
[0066] Using the catalyst performance testing method in Example 1, the catalyst performance was measured as follows: the overall yield of C10-C18 hydrocarbon fuels was 57.54 wt%, and the yield of C10-C18 hydrocarbon-rich biofuels per unit time on the catalyst was 28.77 wt% / (g·h).
[0067] Example 6
[0068] (1) Alkali etching: Weigh 2.0 g NaOH and dissolve it in 100 mL of deionized water. Then add 5.0 g of 20-40 mesh ZSM-5 (silicon-to-aluminum ratio = 50) particles, set the stirring speed to 300 rpm, and immerse the sample at room temperature for 1 h. Subsequently, use dilute acid and deionized water alternately for filtration to remove aluminum material and silicate deposits on the skeleton caused during the alkali treatment, so as to avoid clogging the pores. Finally, place the filtered sample in an oven at 110 ℃ and dry for 6 h.
[0069] (2) Impregnation: Prepare 50 mL of 0.50 mol / L hydroxyethylidene diphosphonic acid monohydrate solution, add 3.0 g of ZSM-5 molecular sieve with a silicon-to-aluminum ratio of 50 under the conditions of 65℃ oil bath and 300 rpm stirring, and impregnate for 2 h. Then, cool the sample in an ice bath and wash it with deionized water until the filtrate is neutral. Dry it at 110℃ for 6 h.
[0070] (3) Calcination: The obtained sample was placed in a tube furnace and heated to 500℃ at a heating rate of 5℃ / min under N2 atmosphere protection. The sample was calcined for 2h to obtain the non-metallic phosphorus modified ZSM-5 molecular sieve catalyst, named: 0.50HEDP@ZSM-5(50), where 0.50 represents the concentration of phosphorus source solution, HEDP represents the type of phosphorus source, and 50 represents the silicon-aluminum ratio of ZSM-5 molecular sieve.
[0071] Using the catalyst performance testing method in Example 1, the catalyst performance was measured as follows: the overall yield of C10-C18 hydrocarbon fuels was 73.01 wt%, and the yield of C10-C18 hydrocarbon-rich biofuels per unit time on the catalyst was 36.51 wt% / (g·h).
[0072] Example 7
[0073] (1) Alkali etching: Weigh 2.0 g NaOH and dissolve it in 100 mL of deionized water. Then add 5.0 g of 20-40 mesh ZSM-5 (silicon-to-aluminum ratio = 50) particles, set the stirring speed to 300 rpm, and immerse the sample at room temperature for 1 h. Subsequently, use dilute acid and deionized water alternately for filtration to remove aluminum material and silicate deposits on the skeleton caused during the alkali treatment, so as to avoid clogging the pores. Finally, place the filtered sample in an oven at 110 ℃ and dry for 6 h.
[0074] (2) Impregnation: Prepare 50 mL of 0.25 mol / L boric acid solution, add 3.0 g of ZSM-5 molecular sieve with a silicon-to-aluminum ratio of 50 under the conditions of 65℃ oil bath and 300 rpm stirring, and impregnate for 2 h. Then, cool the sample in an ice bath and wash it with deionized water until the filtrate is neutral. Dry it at 110℃ for 6 h.
[0075] (3) Calcination: The obtained sample was placed in a tube furnace and heated to 500℃ at a heating rate of 5℃ / min under N2 atmosphere protection. The sample was calcined for 2h to obtain the non-metallic boron modified ZSM-5 molecular sieve catalyst, named: 0.25H3BO3@ZSM-5(50), where 0.25 represents the concentration of boron source solution, H3BO3 represents the type of boron source, and 50 represents the silicon-aluminum ratio of ZSM-5 molecular sieve.
[0076] Using the catalyst performance testing method in Example 1, the catalyst performance was measured as follows: the overall yield of C10-C18 hydrocarbon fuels was 47.51 wt%, and the yield of C10-C18 hydrocarbon-rich biofuels per unit catalyst per unit time was 23.76 wt% / (g·h).
[0077] Comparative Example 1
[0078] 1.0 g of 20-40 mesh ZSM-5 (silicon-aluminum ratio = 50) commercial catalyst was weighed and tested using the catalyst performance test method in Example 1. The catalyst performance was measured as follows: the overall yield of C10-C18 hydrocarbon fuels was 23.03 wt%, and the yield of C10-C18 hydrocarbon-rich biofuels achieved per unit time on the catalyst was 11.52 wt% / (g·h).
[0079] Comparative Example 2
[0080] Alkali etching: Weigh 2.0 g NaOH and dissolve it in 100 mL of deionized water. Then add 5.0 g of 20–40 mesh ZSM-5 (silicon-to-aluminum ratio = 50) particles. Set the stirring speed to 300 rpm and impregnate at room temperature for 1 h. Subsequently, alternately filter and wash with dilute acid and deionized water to remove aluminum and silicate deposits outside the framework caused during the alkali treatment, preventing them from clogging the pores. Finally, place the filtered sample in a 110 °C oven and dry for 6 h to obtain the alkali-etched ZSM-5 (silicon-to-aluminum ratio = 50) catalyst.
[0081] Weigh 1.0 g of 20-40 mesh alkaline-etched ZSM-5 (silicon-aluminum ratio = 50) catalyst and test the catalyst performance using the catalyst performance test method in Example 1. The catalyst performance was measured as follows: the overall yield of C10-C18 hydrocarbon fuels was 25.77 wt%, and the yield of C10-C18 hydrocarbon-rich biofuels achieved per unit catalyst per unit time was 12.89 wt% / (g·h).
[0082] Comparative Example 3
[0083] (1) Alkali etching: Weigh 2.0 g NaOH and dissolve it in 100 mL of deionized water. Then add 5.0 g of 20-40 mesh ZSM-5 (silicon-to-aluminum ratio = 50) particles, set the stirring speed to 300 rpm, and immerse the sample at room temperature for 1 h. Subsequently, use dilute acid and deionized water alternately for filtration to remove aluminum material and silicate deposits on the skeleton caused during the alkali treatment, so as to avoid clogging the pores. Finally, place the filtered sample in an oven at 110 ℃ and dry for 6 h.
[0084] (2) Cu loading: Prepare 50 mL of 0.25 mol / L copper chloride solution, add 3.0 g of ZSM-5 molecular sieve with a silicon-to-aluminum ratio of 50 under the conditions of 65℃ oil bath and 300 rpm stirring, and soak for 2 h. Then, cool the sample in an ice bath and wash it with deionized water until the filtrate is neutral. Dry it at 110℃ for 6 h.
[0085] (3) Calcination: The obtained sample was placed in a tube furnace and heated to 500℃ at a heating rate of 5℃ / min under N2 atmosphere protection. The sample was calcined for 2h to obtain the copper-supported modified ZSM-5 molecular sieve catalyst, named: 0.25CuCl2@ZSM-5(50), where 0.25 represents the concentration of copper source solution, H3BO3 represents the type of copper source, and 50 represents the silicon-aluminum ratio of ZSM-5 molecular sieve.
[0086] Using the catalyst performance testing method in Example 1, the catalyst performance was measured as follows: the overall yield of C10-C18 hydrocarbon fuels was 55.25 wt%, and the yield of C10-C18 hydrocarbon-rich biofuels achieved per unit catalyst per unit time was 27.63 wt% / (g·h); after 3 cycles, the yield of C10-C18 hydrocarbon-rich biofuels achieved per unit catalyst per unit time was 20.29 wt% / (g·h).
[0087] Taking Cu-supported modified ZSM-5 molecular sieve catalyst as an example, it is generally believed that the acidic sites of the metal-supported modified ZSM-5 molecular sieve material are the active centers for catalytic cracking reactions, especially playing an important role in the decarboxylation process. Its catalytic cracking of oils and fats can be divided into three stages: primary cracking, secondary cracking, and polymerization rearrangement, as detailed below:
[0088] The main cracking stage involves the breaking of the CC / C=C bonds in the triglyceride molecule, yielding the corresponding macromolecular fatty acids and oxygen-containing compounds such as ketones, aldehydes, and ethers. This process mainly occurs in the larger pores inside the ZSM-5 molecular sieve catalyst and can be explained by γ-hydrogen transfer and β-elimination mechanisms.
[0089] The secondary cracking stage is characterized by deoxygenation, which mainly occurs through two pathways: decarboxylation and decarbonylation. In the decarboxylation pathway, the carboxyl group in fatty acids is removed, producing linear low-carbon saturated alkanes and carbon dioxide; while decarbonylation removes the carbonyl group to produce alkenes, along with carbon monoxide and water. Additionally, under high-temperature conditions, acids readily form free radicals and undergo carboxylic acid condensation reactions to generate symmetrical ketones. These three reaction pathways are feasible, especially with the introduction of catalysts, which can promote specific routes and thus achieve selective control over the final product distribution.
[0090] The polymerization and rearrangement stage is crucial for the upgrading of biofuels. This stage involves the polymerization reaction of low-carbon olefins and alkanes obtained from secondary cracking under the action of molecular sieve catalysts to generate higher olefins and alkanes, which are the components of biofuel. At the same time, the generated olefins and alkanes can also be transformed into aromatics, heavy oil and coke through processes such as aromatization, cyclization and alkylation.
[0091] Based on the above-mentioned catalytic cracking reaction mechanism, promoting the primary cracking of vegetable oils in the internal channels of ZSM-5 molecular sieves, and controlling the polymerization and aromatization of short-chain olefins and alkanes generated by secondary cracking, is the basic idea for the efficient preparation of biofuels.
[0092] It should be noted that the above theory only considers the effect of introduced metal elements and their compounds on the acid-base properties of molecular sieve materials. With the development of catalysis technology, it has been recognized that different crystal structures also have significant catalytic effects. Metal-supported modified catalysts, after high-temperature calcination, largely alter the crystal structure of ZSM-5 molecular sieves, resulting in a greater diversity of potential active sites and a more complex catalytic pathway. This leads to a more complex composition of alkanes, alkenes, and aromatics in the products, with less controllable carbon chain length. Consequently, the overall yield of C10–C18 hydrocarbon fuels decreases, not only reducing the quality of the product oil but also increasing the difficulty of elucidating the catalytic mechanism.
[0093] Based on this, the non-metallic modified molecular sieve catalyst provided by this invention starts from the adjustment of pore structure and the regulation of acidic site properties, and adopts a strategy of non-metallic element modification. Under the premise of ensuring that the material's crystal structure remains unchanged and the pore structure is reasonable, a non-metallic modified molecular sieve catalyst with clearly defined active site types and properties is prepared. Combined with... Figures 1-5 Multiple characterization methods confirmed that the microstructure of the non-metallic modified molecular sieve catalyst prepared by the method described in this invention still exhibits the three-dimensional spatial structure of the substrate molecular sieve material, but its internal pore size is increased. This process is beneficial to improving the mass transfer effect of the reactants, thereby avoiding the occurrence of excessive cracking reaction. At the same time, it can also effectively alleviate the blockage of catalyst channels by generated coke-like substances and reduce the utilization rate of the active surface of the catalyst, thereby improving the stability and service life of the catalyst (Example 1 and Comparative Example).
[0094] Regarding the analysis of catalytic active sites, since the catalyst provided by this invention does not contain metal-supported components, it effectively avoids introducing crystal structures as potential active sites to catalyze the cracking reaction of woody oils, thus simplifying the analysis of the catalytic mechanism. Figure 2 Furthermore, the non-metallic source material leads to variations in the form and proportion of non-metallic boron and phosphorus atoms on the surface of the resulting modified molecular sieve catalyst. The introduced boron atoms mainly exist in the forms of BO, B-OH, BOO, and BO-Al, while the introduced phosphorus atoms mainly exist in the forms of P=O, P-OH, and PO-Al, thus modulating the acid-base properties of the catalyst surface. Subsequent experimental investigations revealed that the BO-Al / B-OH and P=O / P-OH / PO-Al groups are the main factors affecting catalyst activity.
[0095] Furthermore, as can be seen from the embodiments and comparative examples of the present invention, the effects of alkaline etching and calcination on catalyst performance are reflected in two aspects: First, the higher the alkaline etching intensity, the larger the pore size of the molecular sieve catalyst, but correspondingly, its structural strength will decrease; second, the calcination temperature has a significant impact on the elemental content of the obtained non-metallic modified molecular sieve catalyst, and at the same time, the higher the calcination temperature, the stronger the structural stability of the obtained catalyst.
[0096] Of course, there may be other embodiments of the present invention. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications according to the present invention, but these corresponding changes and modifications should all fall within the protection scope of the claims of the present invention.
Claims
1. The application of a non-metallic modified molecular sieve catalyst in the catalytic cracking of bark oil to produce hydrocarbon-rich biofuels, characterized in that: Under an oxygen-free atmosphere, the oil of the sclerophylla tree was pumped into a catalytic bed containing the above-mentioned molecular sieve catalyst for heated catalytic cracking; The non-metallic modified molecular sieve catalyst comprises a base molecular sieve and a non-metallic element supported on its surface; the non-metallic element is phosphorus or boron, and its mass percentage content is 0.5-8.0% of the total mass of the catalyst; the phosphorus source of the non-metallic element phosphorus is one of hydroxyethylidene diphosphate monohydrate, hexachlorotriphosphazene, and ammonium dihydrogen phosphate; the boron source of the non-metallic element boron is boric acid or boron oxide. The substrate molecular sieve is one of ZSM-5, HZSM-5, SAPO-11 and SAPO-34.
2. The application according to claim 1, characterized in that: The catalyst has an internal pore size larger than the substrate molecular sieve size, ranging from 3 to 10 nm, and a specific surface area of 6 to 100 m². 2 / g.
3. The application according to claim 1, characterized in that: The liquid hourly space velocity (LHSV) of the oil pumped into the tree is 0.10~10.00 h⁻¹. -1 The catalyst bed comprises the aforementioned molecular sieve catalyst and inert quartz sand.
4. The application according to claim 3, characterized in that: The temperature for the heated catalytic cracking is 350~500℃.
5. The application according to any one of claims 1 to 4, characterized in that: The preparation process of the non-metallic modified molecular sieve catalyst is as follows: after the substrate molecular sieve is alkali-etched, it is fully impregnated in a non-metallic element solution, and then calcined under a protective atmosphere to obtain the catalyst.
6. The application according to claim 5, characterized in that: The alkaline etching treatment is carried out at room temperature, and the alkaline etchant is a strongly alkaline solution with a concentration of 0.2~0.5 mol / L; the conditions for full immersion are: temperature of 20~80℃, non-metallic element solution concentration of 0.5~5.0 wt%, and time of 0.5~2h.
7. The application according to claim 5, characterized in that: The protective atmosphere is nitrogen and / or argon; the calcination conditions are: temperature of 400~600℃, time of 2~4h.
Citation Information
Patent Citations
Processing technology for biolipid
CN107964419A
Method for improving stability of ZSM-5 zeolite catalyst for preparation of phenylacetaldehyde by styrene oxide rearrangement
CN110508316A
